Penerimaan Teknologi E-Learning SiPeDar Dengan Menggunakan Technology of Acceptance Model (TAM) - Trio Ardhian; Khotim Hanifudin Najib; Eka Ridha Nofrida; Trisniawati (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
SiPeDar is an e-learning platform developed by UST to facilitate learning from the campus academic community. The application of Information Technology is always related to user acceptance. Therefore, the purpose of this study is to obtain empirical evidence related to the acceptance of SiPeDar technology using the Theory of Acceptance Model (TAM) framework with the construct of perceived ease of use, perceived usefulness, attitude toward using, and acceptance of e-learning system (acceptance of e-learning system). The sample of this study was 77 students from UST Yogyakarta PGSD students who were randomly selected. The data collection technique employed a questionnaire distributed through Gform. The data analysis technique used is quantitative descriptive data analysis using the SPSS program. The results showed that the perceived ease of use of SipeDar and students' perceived usefulness towards SiPeDar were good. The students' attitude towards using SiPedar shows a reasonably good assessment category. SiPeDar's actual system usage shows a high level of usage among students.